Biodistribution of Uranium in Mice and Influencing Factor Preliminary Discussion - Bing, Deng; Jing-Wei, Hou; Lian, Dong; Liang, Dong (Asian Journal of Chemistry, 2014)
The general objective of our work was to preliminary discuss the relationship between uranium(VI) distribution in mice and the speciation of uranium in blood plasma and urine. The results show that, mice were injected with depleted uranium (DU) (5 mg/kg), the important uranium deposit sites are bones, kidneys, liver and spleen. Excretion of uranium mainly through kidney and the concentration of uranium in the liver and spleen have two peaks with time passed. Computer simulation shows that the major uranium species were uranium complex ions at normal blood plasma pH value, which explain the animal experiment phenomenon that uranium removed faster in the blood and the species of uranium in the plasma blood related to the total uranium concentration. The formation of souble uranyl ion with phosphate radical is high solubility solid material, resulting in uranium long-term deposition in bone. Computer simulation also shows the solid phase as (UO2)3(PO4)2·4H2O appeared in the urine, which are toxic to kidneys.